Investigation of brix refractometry for estimating bovine colostrum immunoglobulin G concentration - Sockett, Donald; Breuer, Ryan M.; Smith, Lindsey W.; Keuler, Nicholas S.; Earleywine, Thomas (Frontiers in Veterinary Science, 2023)
This study investigated the utility of a digital Brix refractometer to predict colostrum IgG concentration. First-milking colostrum from 182 animals was analyzed. Statistical analysis, using simple linear regression to relate %Brix results with corresponding colostral IgG concentration, and receiver operating characteristic (ROC) analysis were used to identify %Brix cutoffs that had no false positive results for 25, 50, 75 and 100 g/L. Colostral IgG concentrations from digital Brix refractometry had a R 2 value of 0.818 and a S-value of 21.7 g/L. %Brix scores of 19.0, 22.0, 25.0 and 30.0 percent were found to best estimate minimum colostral IgG concentrations of 25, 50, 75 and 100 g/L, respectively. These four cutoffs can be used to strategically feed smaller volumes of colostrum to newborn calves. This may reduce unwanted side effects and shorten the time interval in which calves refuse to nurse, while still delivering an adequate mass of IgG to have successful transfer of passive immunity.